ASPEK-ASPEK KETAHANAN PADA MASA PEMERINTAHAN RAJA UDAYANA DI BALI - Edi Palguna, I Kadek (Humanis; Volume 8. No. 2. Agustus 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 The reality of endurance conception is arrangement and organizing of welfare and security in balanced, harmonious, and harmony in national life. Endurance at this time may not be the same with the endurance at the ancient Bali in particular on Reign of King Udayana. This study was conducted by using literature data collection methods, and data processing method through some analysis of such as non - physical analysis, qualitative analysis and contextual. Analysis theory has been used in this study that was endurance theory, structural functionalism theory, and theory of government. Based on the analysis, it is known aspects of endurance at the reign of King Udayana that was natural aspects that consist of geography (her, gunung, lanah, and Ranu), natural resources (karambo, sampi, gagan, atak, etc.), and demographic (thani, wanua, and karaman). Social aspects that consist of economy (pken, lagad pasar, gaga, etc.), political (pejebat and bureaucracy), and sociocultural (anak thani,wanua, karaman, undhagi, saiwa sogata etc.). Correlation between the natural aspect with social aspects has been arranged and setting by the King of Udayana and his society at that time, which is by evidence of there is regulations of banning by release by the king. The king of Udayana also determines each village group region with its borders is known with term of parima??ala, to fulfill of its needs. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Endurance, Natural Aspects, Social Aspects, and Interpersonal Aspects.